Disentangling the role of environmental and human pressures on biological invasions across Europe - Pysek, Petr; Jarosík, Vojtech; Hulme, Philip E; Kühn, Ingolf; Wild, Jan; Arianoutsou, Margarita; Bacher, Sven; Chiron, Francois; Didziulis, Viktoras; Essl, Franz; Genovesi, Piero; Gherardi, Francesca; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2010)
The accelerating rates of international trade, travel, and transport in the latter half of the twentieth century have led to the progressive mixing of biota from across the world and the number of species introduced to new regions continues to increase. The importance of biogeographic, climatic, economic, and demographic factors as drivers of this trend is increasingly being realized but as yet there is no consensus regarding their relative importance. Whereas little may be done to mitigate the effects of geography and climate on invasions, a wider range of options may exist to moderate the impacts of economic and demographic drivers. Here we use the most recent data available from Europe to partition between macroecological, economic, and demographic variables the variation in alien species richness of bryophytes, fungi, vascular plants, terrestrial insects, aquatic invertebrates, fish, amphibians, reptiles, birds, and mammals. Only national wealth and human population density were statistically significant predictors in the majority of models when analyzed jointly with climate, geography, and land cover. The economic and demographic variables reflect the intensity of human activities and integrate the effect of factors that directly determine the outcome of invasion such as propagule pressure, pathways of introduction, eutrophication, and the intensity of anthropogenic disturbance. The strong influence of economic and demographic variables on the levels of invasion by alien species demonstrates that future solutions to the problem of biological invasions at a national scale lie in mitigating the negative environmental consequences of human activities that generate wealth and by promoting more sustainable population growth.
Keywords: lidé; Models, Biological; Climate; Regression Analysis; Evropa; savci; Population Dynamics; Ecosystem; Invertebrates; Environment; Human Activities; Humans; populační dynamika; zeměpis; Mammals; vývoj rostlin; životní prostředí; houby; ekosystém; biodiverzita; bezobratlí; biologické modely; zvířata; hustota populace; Fungi; Animals; podnebí; Europe; Geography; Population Density; lidské činnosti; regresní analýza; Biodiversity; Plant Development